PENGARUH KOMUNIKASI INTERPERSONAL GAYA KEPEMIMPINAN TERHADAP KINERJA GURU DI MAS Al HUDA PANGKALAN SUSU - Muhammad Fahmi Alhadi Pane (CV. Arsy Persada Quality, 2025)
At MAS Al Huda Pangkalan Susu there is still a lack of communication and openness between the principal and teachers. The principal rarely participates in school activities. There is a gap between teachers and school principals. The principal's lack of communication attitude causes the organizational culture to be poor so that groupings form between teachers. Principals should work together with teachers. Through interpersonal communication, the principal can embrace the teacher as a whole. So that a good organizational culture will be created in the school environment.Research objectives: determine the influence of interpersonal communication on teacher performance, determine the influence of leadership style on teacher performance, determine the influence of organizational culture on teacher performance, and determine the influence of interpersonal communication, leadership style, organizational culture on teacher performance.The research was conducted at MAS Al Huda Pangkalan Susu from January - March 2024. This research is quantitative research, the population and sample size are the same, namely 12 people, using the Totally Sampling method. There is a positive and significant influence of interpersonal communication on teacher performance. amounting to 29.3%. There is a positive and significant influence of organizational culture on teacher performance of 71.0%. There is a positive and significant influence of leadership style on teacher performance of 70.9%. There is a positive and significant influence between interpersonal communication, organizational culture, leadership style together on teacher performance of 78.9%.